2019
DOI: 10.1007/s10404-019-2251-9
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of fluid type and particle shape on particles flow in microfluidic platforms

Abstract: Recent numerical analyses to optimize the design of microfluidic devices for more effective entrapment or segregation of surrogate circulating tumor cells (CTCs) from healthy cells have been reported in the literature without concurrently accommodating the non-Newtonian nature of the body fluid and the non-uniform geometric shapes of the CTCs. Through a series of two-dimensional proof-of-concept simulations with increased levels of complexity (e.g., number of particles, inline obstacles), we investigated the v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Since the LBM is a weakly compressible scheme, it is not very accurate for the pressure field, which may negatively affect the lift and drag forces acting on moving particles. Although recent LBM studies have shown considerable progress in enhanced computational performance, nonspherical particles (using DSP-LBM method), or non-Newtonian fluids, [137][138][139][140] more research is needed to investigate the accuracy and reliability of the LBM for inertial particle microfluidics.…”
Section: Concluding Remarks and Outlookmentioning
confidence: 99%
“…Since the LBM is a weakly compressible scheme, it is not very accurate for the pressure field, which may negatively affect the lift and drag forces acting on moving particles. Although recent LBM studies have shown considerable progress in enhanced computational performance, nonspherical particles (using DSP-LBM method), or non-Newtonian fluids, [137][138][139][140] more research is needed to investigate the accuracy and reliability of the LBM for inertial particle microfluidics.…”
Section: Concluding Remarks and Outlookmentioning
confidence: 99%
“…The LBM formulation above has been commonly used to simulate flow of circular-cylindrical particles in Newtonian fluid flow. The extension of the model to simulate settling or flow trajectories of 2D angular-shaped (e.g., boomerang-, star-, rectangular-, hexagonal-shaped particles) and circular-shaped (e.g., elliptical) particles in Newtonian or non-Newtonian fluid flow were provided by Başağaoğlu et al [145,146]. In the coupled IBM-LBM, the IBM is typically used to calculate the FSI forces, and LBM is used to simulate the flow field by incorporating the FSI as the source term in the LB equation.…”
Section: Lattice Boltzmann Methods (Lbm)mentioning
confidence: 99%
“…Their simulations revealed that any irregularity on wall surfaces could cause temporary or permanent clogging of the flow field if hydrodynamic forces on the particle cannot overcome unevenly distributed repulsive barrier on the channel wall. Başağaoğlu et al used the LJ 6-12 model to simulate chemotatic motility [220] or flow [221,222] of circular particles in a Newtonian fluid, settling or flow of a mixture of non-circular particles in a Newtonian fluid, and flow of a mixture of non-circular particles in a non-Newtonian fluid [145,146]. Using the LJ 6-12 potentials, Başağaoğlu et al [146] demonstrated that steady vortices do not necessarily always control particle entrapments nor do larger particles get selectively entrapped in steady vortices in a microfluidic chamber.…”
Section: Lennard-jones Potentialsmentioning
confidence: 99%
“…It has also previously been shown, both computationally and experimentally, that the shape of rigid particles can influence their migration patterns in a microchannel (43)(44)(45)(46). It is quite likely that it will similarly affect deformable particles such as cells.…”
Section: Introductionmentioning
confidence: 93%